3D printing of wood fibre biocomposites: From mechanical to actuation functionality. (15th April 2016) - Le Duigou, A.; Castro, M.; Bevan, R.; Martin, N.
Abstract: Natural fibres are increasingly used as reinforcements for thermoplastic composites. Additive manufacturing, also known as 3D printing, is a common material extrusion process using (bio)polymers reinforced with natural fibres. However, there is a lack of understanding of the effect of printing parameters on the mechanical properties involved in this new process, and more particularly in the case of Fused Deposition Modeling (FDM). Hygromorphic biocomposites represent a novel use of natural fibres for the production of original self-bending devices that actuate in a moisture gradient. By mimicking natural actuators and their bilayer microstructure adapted for seed dispersal, hygromorphic biocomposites take advantage of the hygro-elastic behaviour of natural fibres. The FDM of wood fibre reinforced biocomposites leads to mechanical properties that are strongly dependent on printing orientation (0 or 90°) due to fibre anisotropy. Mechanical properties depend also on printing width (overlapping of filaments), with a lower Young's modulus than in the compressed samples. Indeed, printed biocomposites have a microstructure with relatively high porosity (around 20%) that conjointly leads to damage mechanisms but also water absorption and swelling. The FDM of hygromorphic biocomposites enables a shift towards 4D printing since the material is able to evolve over time in response to an external stimulus. Typical microstructures achieved by printing could be used advantageously to produce biocomposites with a faster moisture-induced bending response compared to compressed samples. Graphical abstract: Highlights: Fused Deposition Moulding (FDM) of wood biocomposites is performed. Mechanical properties and microstructure are characterized according to printing width and orientation. Mechanical properties are relatively low due to high porosity level located in interlayer area. Hygromorph biocomposites are designed following bio-inspiration approach. Porosity induced by FDM could be turned as an advantage when hygromorph biocomposites is developed.